Antiretroviral Therapy–Induced Mitochondrial Toxicity: Potential Mechanisms Beyond Polymerase‐γ Inhibition. Issue 1 (17th March 2014) - Selvaraj, S; Ghebremichael, M; Li, M; Foli, Y; Langs‐Barlow, A; Ogbuagu, A; Barakat, L; Tubridy, E; Edifor, R; Lam, W; Cheng, Y‐C; Paintsil, E
<x xml:space="preserve">Abstract</x> We hypothesized that competition between nucleotide reverse‐transcriptase inhibitor triphosphate and endogenous deoxyribonucleotide triphosphate (dNTP) may lead to depletion of dNTP pools and mitochondrial dysfunction independent of polymerase‐γ (pol‐γ) inhibition. We collected peripheral blood mononuclear cells from 75 adults (25 cases: HIV‐infected patients with mitochondrial toxicity, 25 HIV‐infected positive controls, and 25 HIV‐negative controls). We observed statistically significant individual and group differences in ribonucleotide (RN) and deoxyribonucleotide (dRN) pools. The median values for the RN pools were 10, 062 (interquartile range (IQR): 7, 090–12, 590), 4, 360 (IQR: 3, 058–6, 838), and 2, 968 (IQR: 2, 538–4, 436) pmol/106 cells for negative controls, positive controls, and cases, respectively. Cases had significantly higher absolute mitochondrial DNA copy number as compared with negative controls (P < 0.05). Moreover, cases had significantly higher expression levels of pol‐γ, nucleotide transporters, cellular kinases, and adenosine triphosphate (ATP)–binding cassette (ABC) proteins as compared with controls. Antiretroviral therapy (ART) perturbs RN and dRN pools. Depletion of RN and dRN pools may be associated with ART‐induced mitochondrial toxicity independent of pol‐γ inhibition. Clinical Pharmacology & Therapeutics (2014); 96 1, 110–120. doi:10.1038/clpt.2014.64